The mediating effect of corporate performance on the influence of intellectual capital and perceived environmental uncertainty on capital structure - Soheilirad, Somayeh (2016)
Understanding and determining capital structure are important for developing countries because firms in the countries are faced with highly competitive and dynamic environment. Financial accounting literatures have highlighted the important role of non-financial factors such as intellectual capital (IC) as a main value added factor for companies, and perceived environmental uncertainty (PEU) as unpredictable contingency factor from a dynamic environment on corporate performance. Therefore, it is important for organizations rely more on non-financial than financial factors to achieve higher competitive advantage. Moreover, the relationship between corporate performance and capital structure is strong. Due to the influence of non-financial factors of IC and PEU on corporate performance, capital structure decision making will be difficult. Identifying the most important non-financial factors affecting corporate performance from these environments and their relationship with capital structure is the main issue in today’s dynamic conditions. This research examined the relationship between non-financial factors of IC and PEU and evaluated their influence on capital structure directly or indirectly by considering corporate performance as mediator. Questionnaires were distributed to 339 public listed Iranian manufacturing companies selected by census. Data were analyzed using structural equation modeling. The main findings of this study are IC can enhance corporate performance, PEU is positively linked to corporate performance, and corporate performance is positively linked to capital structure. The results also indicated a full mediating role of corporate performance in the relationship between PEU and capital structure. This study contributes to determining capital structure decision making, by considering IC and PEU in the context of companies in Iran. Further in-depth research is needed to examine the links between non-financial factors with different measurement perspectives and capital structure to develop a deeper understanding of their effect on capital structure.